2015
DOI: 10.1021/jacs.5b09337
|View full text |Cite
|
Sign up to set email alerts
|

Single Nanoparticle to 3D Supercage: Framing for an Artificial Enzyme System

Abstract: A facile strategy has been developed to fabricate Cu(OH)2 supercages (SCs) as an artificial enzyme system with intrinsic peroxidase-mimic activities (PMA). SCs with high catalytic activity and excellent recyclability were generated via direct conversion of amorphous Cu(OH)2 nanoparticles (NPs) at room temperature. More specifically, the process that takes a single nanoparticle to a 3D supercage involves two basic steps. First, with addition of a copper–ammonia complex, the Cu2+ ions that are located on the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 35 publications
0
65
0
1
Order By: Relevance
“…[4,5] To overcome the above-mentioned problems,artificial enzymes with lower cost and higher stability than natural enzymes have become an alternative to natural enzymes. [8][9][10][11][12][13][14][15][16][17] So far, av ariety of nanomaterials,s uch as iron oxide nanoparticles,p russian blue nanoparticles,v anadium oxide nanoparticles,ceria nanoparticles,noble metal nanoparticles, and nanocarbon materials (CNMs) have been discovered to possess enzyme-like catalytic activities. [8][9][10][11][12][13][14][15][16][17] So far, av ariety of nanomaterials,s uch as iron oxide nanoparticles,p russian blue nanoparticles,v anadium oxide nanoparticles,ceria nanoparticles,noble metal nanoparticles, and nanocarbon materials (CNMs) have been discovered to possess enzyme-like catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] To overcome the above-mentioned problems,artificial enzymes with lower cost and higher stability than natural enzymes have become an alternative to natural enzymes. [8][9][10][11][12][13][14][15][16][17] So far, av ariety of nanomaterials,s uch as iron oxide nanoparticles,p russian blue nanoparticles,v anadium oxide nanoparticles,ceria nanoparticles,noble metal nanoparticles, and nanocarbon materials (CNMs) have been discovered to possess enzyme-like catalytic activities. [8][9][10][11][12][13][14][15][16][17] So far, av ariety of nanomaterials,s uch as iron oxide nanoparticles,p russian blue nanoparticles,v anadium oxide nanoparticles,ceria nanoparticles,noble metal nanoparticles, and nanocarbon materials (CNMs) have been discovered to possess enzyme-like catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…From these plots,s ome important kinetic parameters including apparent Michaelis-Menten constant (K m ), maximum initial velocity (V max ), and catalytic constant (K cat )c an be estimated (Table 1). Thea pparent K m of TMB,OPD,DA, and NADH is 0.94 mm,8.88 mm,0.47 mm, and 0.37 mm,r espectively.F or the TMB oxidation reaction, the apparent K m value is lower than the value of 1.63 mm with of zirconium-metalloporphyrin( PCN-222), and 2.448 mm with Cu(OH) 2 supercages [29] as mimic peroxidases.Moreover, the apparent K cat values of Cu@Cu 2 Owith TMB and OPD are higher than the values of 14.0 min À1 ,7.3 min À1 with PCN-222 and 0.1 min À1 ,0 .8 min À1 with hemin as catalyst, respectively. [5a, 30] Thefast rate of such acatalytic reaction is ascribed to the high surface area and the exposed activity sits in Cu@Cu 2 Oa erogel networks.…”
mentioning
confidence: 99%
“…Peroxidase-like activity of CoFe-layered double hydroxides was reported by Sun et al, who further used CoFe hydroxides for colorimetric detection of H 2 O 2 and glucose [64]. Recently Tan et al reported a very efficient peroxidase-mimic system based on nanocages of Cu(OH) 2 , which showed more peroxidase-like activity than natural enzymes [65]. Metal chalcogenides are another class of nanomaterials which has been explored for their enzyme-like activities.…”
Section: Types Of Nanomaterialsmentioning
confidence: 99%